Perceptions of Anxiety in Speaking English Among Students - Sukarno, Berliana Sukma Tri; Fitria, Sri Ade; Kurniawan, Ricky Ilham; Iskandar, Andy Basoka (Journal of English Education Program, 2025)
This study examines how students perceive anxiety when speaking English at Senior High School. It specifically focuses on text anxiety in formal situations and aims to pinpoint the most prominent indicators of this anxiety. The study's theoretical framework centers on the concept of speaking, encompassing its definition, elements, characteristics, components, and functions. Additionally, it delves into anxiety, covering its definition, types, symptoms, and underlying factors. Employing a quantitative research method, the methodology involves used a questionnaire to gather data from students, which is then analyzed using statistical methods to unveil key findings regarding anxiety indicators in English speaking among senior high school students. The implications of these findings are significant for educators and policymakers, providing insights that can guide targeted interventions aimed at improving the language learning experience, building confidence, and enhancing effective English communication skills among students.